The snow angel - Leeson, Christine, 1965- (Tiger Tales, 2007)
While playing in the snow on Christmas morning, Daisy and Sam Mouse see an "angel" fall from the sky, and when they share their Christmas treats to help it revive, the goose leaves a special present behind.